Critiquing communication innovation new media in a multipolar world - Hoyng, Rolien; Chong, Gladys Pak Lei, 1977- (US-China relations in the age of globalization., 2022)
"While China has been rising as an innovative platform society and AI powerhouse, this book addresses the broader question of a shifting world order and trends that are shaped by China's influence but extend beyond its borders"--